Analisis Pengalaman Wisatawan terhadap Minat Berkunjung Kembali melalui Customer Satisfaction sebagai Variabel Intervening (Survei pada Wisatawan di Kabupaten Sukabumi) - Rizky Awalul Gunawan; Asep Muhamad Ramdan; Sopyan Saori (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Recurring visits to local tourist places are declining, which highlights the need for a deeper understanding of what draws visitors back. Revisit intention is said to be significantly influenced by the visitor experience, especially when it results in consumer pleasure. Using customer satisfaction as an intervening variable at tourist locations in Sukabumi Regency, this study attempts to examine the impact of tourist experience on revisit intention. In this study, a quantitative associative approach was used. A structured questionnaire was used to gather data from 150 tourists who were chosen through purposive sampling. SmartPLS 3.2.9 software was used to analyze the data using the Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. The findings indicate that tourist experience has a positive and significant effect on customer satisfaction and revisit intention. Customer satisfaction also shows a significant positive effect on revisit intention. Moreover, the mediation analysis demonstrates that customer satisfaction plays an important role in strengthening the relationship between tourist experience and revisit intention. These results suggest that improving tourists’ overall experience can enhance satisfaction levels, which subsequently increases the likelihood of repeat visits to the destination.